Effective Length of Columns in Gable Frames - Lu, Le-Wu (Engineering Journal, 1965)
Usually, single-story, shed-type buildings utilizing gable frames are braced normal to these frames or otherwise receive lateral support so that sidesway in this direction is inhibited. On the other hand, single story gabled frames are not braced against sidesway parallel to the plane of the frames. In the design of columns, the 1963 AISC Specification requires that an effective length factor larger than unity be used when computing the slenderness ratio in a plane where the frame is not prevented from sidesway.